Managing tensions between exploitative and exploratory innovation through purchasing function ambidexterity. Issue 4 (October 2020) - Constant, François; Calvi, Richard; Johnsen, Thomas E.
Abstract: This paper investigates how companies can manage tensions between exploitative and exploratory innovation by developing an ambidextrous purchasing function. We identify four types of ambidexterity (structural, sequential, contextual and managerial) and discuss how these can be combined to complement each other. We present an in-depth case study of a large firm (S Corp), which has implemented an ambidextrous purchasing function to contribute simultaneously to exploitative and exploratory innovation. We observe how the four types of ambidexterity were manifested and applied to balance purchasing's contribution to both exploratory and exploitative innovations. The case study shows how the different types of ambidexterity can be combined to mitigate tensions. Based on our case study findings, we identify a two-stage process of developing purchasing ambidexterity, combining the four types of ambidexterity over time. Our findings enrich the understanding of how companies can develop an ambidextrous purchasing function to facilitate purchasing's contribution to exploitative innovation and exploratory innovation. Highlights: Purchasing ambidexterity is a concept investigating how purchasing can balance explorative and exploitative activities in innovation. Purchasing ambidexterity is a combination of 4 types of ambidexterity (structural, sequential, contextual and managerial). Contextual and managerial ambidexterity support structural and sequential ambidexterity. Our case has implemented structural and sequential ambidexterity prior to implement contextual and managerial ambidexterity. A combined purchasing ambidexterity reduces tensions occurring within and across the four types of ambidexterity..